Clinico-haemato-biochemical changes in naturally occurring canine babesiosis in Punjab, India - Suresh, Gonde (2019)
A comprehensive study was conducted on the clinical observations including clinical history, physical examination along with haematobiochemical alteration on 41 naturally occurring cases of canine babesiosis from Punjab state, India. Examination of 964 dogs revealed 4.25 percent (41/964) prevalence of the disease including 3.84 percent (37) B. gibsoni and 0.41 percent (4) B. canis infected cases. Clinical and parasitological diagnosis was finally confirmed by polymerase chain reaction. A large variation of clinical anifestations including rare findings of paraplegia, blindness, ocular bleeding, immune mediated haemolytic anaemia (IMHA), ascites and skin lesions were observed among the affected animals. Blood films showed anisocytosis and nucleated erythrocytes indicating regenerative anaemia. Blood parameters of the affected dogs revealed significant decrease in Hb, TEC, PCV and thrombocytes. Significant decrease in lymphocytes was found in B. gibsoni affected animals. The affected dogs showed significant increase in serum bilirubin, ALT, AKP, BUN and creatinine. Haemato-biochemical observations were indicative of severity of babesiosis in dogs.